Reviving Lydia Huntley Sigourney - Dasler Johnson, Wendy (Romanticism on the Net)

(untitled) (Université de Montréal, 2003)
AbstractLydia Sigourney’s (mis)identification as “The American Hemans” serves as a kind of parallel or allegory for the double-bind faced by nineteenth-century woman writers: to become famous, one must be like Hemans, but to be like Hemans is to lose sight of oneself; to signify oneself as a “proper” woman writer, one must utter the sobs of the sentimental woman, but such a voice has been valued by critics at about the level of “anonymous.” Sentimentalism, what is expected of the woman writer if she is to achieve fame, has been seen as manipulation, not an art. In a feminist prose essay on women’s education, Sigourney reveals her desire for fulfillment in roles other than the strictly domestic: she longs for the day when women can be “professors.” A canny poet-engineer taking up the tools of the new sensationist epistemology to become a professor of sentimental rhetoric, Sigourney deploys several poetic voices or personae to communicate her decidedly feminist ethos. The subject positions adopted in her poems are various, ranging from male seminary professor to an edgy, angry, male prophet, from woman rhetor to woman preacher. In Lucy Howard’s Journal, Sigourney prophesies and in some sense prepares her own reception history as a female writing subject whose textual voice can outlive the stultifying critique of feminine sentimentalism.